The Influence of Internal Control Systems, Motivation, and Remuneration on the Prevention of Fraud in the Misuse of Funds in Local Government - Frendy, Frendy; Pruyudo, Bayu; Suratminingsih, Suratminingsih; Pangaribuan, Leonard (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
This study aims to determine the alignment between the implementation of the Internal Control System (SPI) in financial management and Government Regulation No. 60 of 2008. It conducts quantitative research by identifying indicators and dimensions for measuring variables that can be analyzed using statistical tools. Currently, there is still limited research on audit based on internal control systems in government, making this research topic interesting to explore further in terms of the effectiveness of internal control in preventing fraud in government, supported by an internal control system. It identifies the factors causing fraud and analyzes the relationship between the achievement of the Internal Control System (SPI). The sample size is 93 people in the Government of West Bangka Regency. The data analysis method uses IBM SPSS Statistics 20 software. The results of this study show that Internal Control has a significant effect on Fraud Prevention. Motivation and Remuneration do not have a significant effect on Fraud Prevention. Simultaneously, the influence of Internal Control Systems, Motivation, and Remuneration on Fraud Prevention is obtained.